2015
DOI: 10.3928/01477447-20150204-57
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Related Factors Influencing Ulnar-Shortening Osteotomy Outcomes Using the Trimed Dynamic Compression Plate

Abstract: Ulnocarpal impingement can be surgically managed with various shortening osteotomy techniques. The purpose of this study was to retrospectively examine the outcomes of the ulnar-shortening osteotomy technique using the Trimed dynamic compression plate (Valencia, California) and to determine whether results vary among patient-related factors, including smoking status, occupation, preoperative diagnosis, and workers' compensation status. Twenty-seven patients (28 wrists) operated by a single surgeon underwent ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Although insurance status was accounted for in the multivariate analysis, socioeconomic status and access to care were unable to be controlled for and are factors that previous authors have suggested may be responsible for observed race-related differences [13]. Worker's compensation claims as an independent risk factor for reoperation (OR 1.7, 1.54-1.88) is relatively novel in such a large cohort registry study and is in line with previous authors' reports that workers' compensation is associated with lower subjective outcomes after ACLR [8], mirroring reports across other orthopaedic subspecialties [3,4,60].…”
Section: Discussionsupporting
confidence: 81%
“…Although insurance status was accounted for in the multivariate analysis, socioeconomic status and access to care were unable to be controlled for and are factors that previous authors have suggested may be responsible for observed race-related differences [13]. Worker's compensation claims as an independent risk factor for reoperation (OR 1.7, 1.54-1.88) is relatively novel in such a large cohort registry study and is in line with previous authors' reports that workers' compensation is associated with lower subjective outcomes after ACLR [8], mirroring reports across other orthopaedic subspecialties [3,4,60].…”
Section: Discussionsupporting
confidence: 81%
“…A large study of 325 USO from South Korea 21 found smoking to be an independent variable to predict nonunion when comparing patients who achieved bony union to those that did not. However, other studies have not found an association with nonunion in smokers, 4,12,15 but they were all smaller studies not designed for subgroup analysis.…”
Section: Discussionmentioning
confidence: 96%
“…The majority of studies of USO describe 4 to 6 weeks of immobilization before active range of movement and strengthening exercises are started. 4,10,13,15,17,20,21 Therefore, arguably all patients in our study were subject to early active mobilization with a 100% union rate. In a study from Belgium, 5 28 USOs were allowed mobilization immediately postoperatively and had a nonunion rate of 11% (3/28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42][43][44][45] Locking plates have shown a nonunion rate of 0 to 14.3%, with an average bone healing duration of 7 to 11 weeks. [46][47][48][49] Although the nonunion rate and the bone healing duration seem to be extended with nonlocking plates, drawing statistical conclusions remains difficult. Furthermore, due to many inconsistencies in definitions of both nonunion and delayed union across various studies, higher-level clinical research is required to unify these definitions and assist surgeons in determining the optimal plate type for the USO procedure.…”
Section: Imaging Examinationmentioning
confidence: 99%